Identité migrante et ses manifestations discursives dans Trilogia de Marco Micone - Wołowski, Witold; Jakubczuk, Renata (Studia Romanica Posnaniensia, 2024)
This article – focused on three plays that make up Marco Micone’s dramatic trilogy (Gens du silence, Addolorata, Déjà l’agonie) – consists of two parts. First, it outlines the historical-political environment of Quebec in the context of immigration and identity issues. Then, the article analyzes some compositional and linguistic aspects – micro- and macrostructural – linked to the migrant identity of the protagonists (monology, adialogism, plurilingualism, metalinguism).